Analysis and evaluation of employee performance assessment system using the PIECES method at PT. Citra Pesona Gemilang - Tri Hartati; Noer Hikmah; Leliyanah Leliyanah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Sumber daya manusia (SDM) are one of the valuable assets owned by institutions/companies to achieve business goals and develop prospects for progress of institutions/companies so that HR plays an important role in decision making at the top level management. Employee performance is also a trigger for the success or failure of an institution/company in running its business. Employee performance appraisal is a step to find out the quality of an employee, what kind of work behavior and how loyal he is to his job. With the employee performance appraisal, the institution/company can determine the policies that will be applied to the employee, such as providing incentives, promotion to promotions, providing training and developing the capabilities of employees. This research focuses on the analysis of the evaluation of the employee performance appraisal system at PT Citra Pesona Gemilang using the PIECES analysis method. This method is used to evaluate the feasibility of implementing the system on the results of employee performance appraisals so as to increase employee productivity. The PIECES method framework that will be discussed in this research is Performance, Information, Economy, Control, Efficiency, Service. This framework will be an indicator of the ongoing analysis and evaluation of information systems